2016
DOI: 10.1038/srep22579
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptor 9 Can be Activated by Endogenous Mitochondrial DNA to Induce Podocyte Apoptosis

Abstract: Toll-like receptor 9 (TLR9) senses bacterial DNA characteristic of unmethylated CpG motifs to induce innate immune response. TLR9 is de novo expressed in podocytes of some patients with glomerular diseases, but its role in podocyte injury remains undetermined. Since TLR9 activates p38 MAPK and NFkB that are known to mediate podocyte apoptosis, we hypothesized that TLR9 induces podocyte apoptosis in glomerular diseases. We treated immortalized podocytes with puromycin aminonucleosides (PAN) and observed podocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 34 publications
4
75
2
Order By: Relevance
“…22 Other studies also confirm the activation of NFKB signal pathway in the immune cells of IgAN patients. 23,24 However, different from these findings in IgAN, in our study, NFKB1 was found to be downregulated in MN samples compared with the control. It might be inferred that the NFKB pathway might be inhibited by other regulators in MN development.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…22 Other studies also confirm the activation of NFKB signal pathway in the immune cells of IgAN patients. 23,24 However, different from these findings in IgAN, in our study, NFKB1 was found to be downregulated in MN samples compared with the control. It might be inferred that the NFKB pathway might be inhibited by other regulators in MN development.…”
Section: Discussioncontrasting
confidence: 99%
“…TLR are demonstrated to be associated with IgAN, and activation of TLR could trigger the transcription factor NFKB . Other studies also confirm the activation of NFKB signal pathway in the immune cells of IgAN patients . However, different from these findings in IgAN, in our study, NFKB1 was found to be downregulated in MN samples compared with the control.…”
Section: Discussioncontrasting
confidence: 61%
“…Our study presented that lowering ROS level could inhibit LPS mediated mtDNA damage in cardiomyocytes, which was consistent with the study that peroxyauraptenol(PXT) significantly inhibited inflammation and NLRP3 inflammasome in LPS activated macrophages by preventing ROS generation and the release of mtDNA [37]. MtDNA can also directly induce cell apoptosis by targeting TLR9, as showed in podocyte, HUVECs and cardiomyocytes [21, 23, 38]. In our EAM model, TLR9 expression in myocardium was obviously increased.…”
Section: Discussionsupporting
confidence: 87%
“…93 TLR9 recognises unmethylated CpG in the endosomal system, 94,95 including that of mitochondrial origin following mitochondrial disruption. [96][97][98][99] CpG recognition by TLR9 provides a signal 1 for NLRP3 activation, transcriptionally upregulating inflammasome-required genes under NF-jB control 100,101 (Figure 3b). The mitochondrial dynamics that drive disruption and exposure of mtDNA to TLR9 are varied and unclear, yet some evidence implicates defective fission/fusion dynamics.…”
Section: Tlr9 Senses Endosomal Cpg Dnamentioning
confidence: 99%